A benign psoas teratoma of the non‐pelvic retroperitoneal space: A case report. Issue 5 (21st January 2013) - Durand, P.; Malone, A.; Courtney, D.
<x xml:space="preserve">Abstract</x> This case report is of a benign retroperitoneal teratoma which was adherent to the psoas muscle of a 53‐year‐old female cadaver with a history of metastatic bladder cancer as a cause of death. Teratomas possess derivatives of all three germ cell layers and are usually seen either in children or in the lower pelvic region of adults. The finding of this mass deep to the inferior pole of the kidney is quite unusual. Few studies mention a possible association between metastatic cancer and teratoma growth in extrapelvic locations. The following report is a detailed account of this unusual finding and a summary of the literature on growths of this kind. Clin. Anat. 26:638–640, 2013. © 2013 Wiley Periodicals, Inc.